Effect of wheat bran dietary fiber on structural properties and hydrolysis behavior of gluten after synergistic fermentation of Lactobacillus plantarum and Saccharomyces cerevisiae - Wang, Zhen; Ma, Sen; Li, Li; Huang, Jihong (Frontiers in Nutrition, 2022)
The effect of synergistic fermentation of Lactobacillus plantarum and Saccharomyces cerevisiae on the structural properties and aggregation behavior of gluten containing different wheat bran dietary fiber (WBDF) levels (0, 3, 6, 9 & 12%) was investigated. The results showed that WBDF addition affected the aggregation behavior of gluten at the molecular level, while WBDF significantly induced depolymerization behaviors in large aggregated gluten proteins (Molecular weight > 130 kDa) under reducing conditions (p < 0.05). In terms of secondary structure, WBDF significantly reduced glutamine side chain levels and reduced antiparallel β-sheet structures from 28.57% to 24.53% (p < 0.05). In addition, WBDF thermal properties and its water holding capacity were the main factors causing changes in thermal properties in the overall gluten system. This study provides new data for the improved production of sourdough whole grain and/or high fiber flour products.